In Vitro Evaluation of the Marginal and Internal Accuracy of Different Types of Dental Ceramic Restorations Fabricated Based on Digital and Conventional Impressions - TÜRKER, ŞEBNEM BEGÜM (QUINTESSENCE PUBLISHING CO INC, 2021)
Purpose: To compare the marginal and internal gap values of different types of ceramic crowns fabricated based on digital and conventional impression methods. Materials and Methods: Ten noncarious extracted human teeth were prepared, and 60 restorations were made using six different impression and fabrication methods. Silicone replicas were obtained for marginal and internal gap evaluation. Statistical analyses were performed using Mann-Whitney U and Kruskal-Wallis tests (P < .05). Results: Statistically significant differences were found among various impression and fabrication methods. The smallest gap value was shown by the monolithic zirconia indirect digital scanning group (31.13 mu m), and the largest for the lithium disilicate indirect digital scanning group (90.09 mu m). Conclusion: The marginal and internal gap values of the restorations in the present study were 31.13 to 90.09 mu m. The marginal and internal discrepancies of the tested materials were considered clinically acceptable.
Keywords: FIXED PARTIAL DENTURES; CLINICAL-EVALUATION; FIT; ADAPTATION; CROWNS; COPINGS; METAL; SYSTEMS; MICROLEAKAGE; PROSTHESES